2017
DOI: 10.5847/wjem.j.1920-8642.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The association of layperson characteristics with the quality of simulated cardiopulmonary resuscitation performance

Abstract: BACKGROUND: Few studies have examined the association of layperson characteristics with cardiopulmonary resuscitation (CPR) provision. Previous studies suggested provider characteristics, including age and gender, were associated with CPR quality, particularly chest compression (CC) depth. We sought to determine the association of subject characteristics, including age and gender with layperson CPR quality during an unannounced simulated CPR event. We hypothesized shallower CC depth in females, and older-aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…A study using CPR quality data stored by automated external defibrillators showed limitations including Emergency Medicine International no bystander information and inclusion bias [14]. Assessment of simulated CPR could not reflect the situation of a real population [15,16]. Takei et al evaluated bystanders in a single area [11].…”
Section: Discussionmentioning
confidence: 99%
“…A study using CPR quality data stored by automated external defibrillators showed limitations including Emergency Medicine International no bystander information and inclusion bias [14]. Assessment of simulated CPR could not reflect the situation of a real population [15,16]. Takei et al evaluated bystanders in a single area [11].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are thought to be due to the influence of other factors, such as the age, sex, BMI, and previous education of bystander, as reported in previous studies. [ 8 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[3] Bystander CPR doubles the odds of survival compared to no CPR. [4] All staff who work in a health care setting, both clinical and non-clinical, have a duty to maintain their BLS skills annually in the event of a cardiac arrest occurring in their workplace. [5] The UK Resuscitation Council and the General Medical Council (GMC) provide clear guidelines regarding the level of training required of medical graduates on graduation.…”
Section: Introductionmentioning
confidence: 99%